Radiation induced defects in graphite - Bradley, D.A. *; Lam, Siok Ee *; Siti Nuraisah, Mat Nawi *; Abdul Sani, S. F.; Khandaker, Mayeen Uddin *; Alzimami, K.; Jambi, L.; Alqahtani, A. (Elsevier Ltd, 2022)
We provide retrospective analysis of a consolidated set of confocal Raman microspectrometry and photoluminescence data for irradiated graphitic materials, detecting the generation of low-dose defects. Within the dose range 0.1 Gy–0.2 kGy, one attracting marginal attention in previous radiation damage studies, an effect is seen that potentially seeds material weakening, the pooled data covering independent x-, gamma-rays, and thermal neutron field irradiations. Categorised in terms of a number of key influencing factors, an emergent pattern of response for the various samples under study is observed, indicative of the cycling of radiation driven energy storage and subsequent relaxation. This novel technique, to be referred to herein as defectroscopy, provides a probe of the generation of radiation-induced defects and internal annealing, the strength of the effects being strongly identified to arise from a combination of the ratio of surface area to volume of the samples, fractional carbon content, linear energy transfer, and strain-related defects within the initial material. These examinations offer a first step in considering whether the technique offers wider applicability, not least in early determination of changes in materials with widespread importance in structural and functional roles. © 2022 Elsevier Ltd